International Analysis of LVAD Point-of-Care Versus Plasma INR: A Multicenter Study. Issue 6 (November 2018) - Schettle, Sarah; Schlöglhofer, Thomas; Zimpfer, Daniel; Schima, Heinrich; Kaufmann, Friedrich; Salimbangon, Anthony; Wolforth, Jennifer; Schroeder, Sarah; Hards, Rachel; Ritchie, Brianne; Staley, Linda; Pereira, Naveen; et al.
Abstract : International normalized ratio (INR) measurements manage risks of bleeding and clotting sequelae in the population with left ventricular assist device (LVAD). Studies suggest that point-of-care (POC) INR does not significantly differ from plasma INR (P-INR) values in other patient populations, although this has not been validated in a multicenter LVAD study. We sought to determine whether POC-INR and P-INR values differ significantly in the LVAD population and reviewed patients with permanent LVAD implantation at seven institutions internationally. Our cohort comprised of 279 paired POC-INR and P-INR checks in patients supported on average 630 ± 598 days postimplant with predominately HeartWare, HeartMate II, and HeartMate III devices. The population averaged 57.9 years of age, and there were 86.7% male. We found no statistically significant difference between POC-INR and P-INR values. International normalized ratio accuracy correlated weakly with the time between INR measurements ( p < 0.001). When the time difference was less than 4 hours, the difference between INR pairs was significantly lower than measurements greater than 8 hours ( p = 0.006). There was no statistically significant difference when comparing paired INR values and time after implant to INR check ( p = 0.43), age ( p = 0.12), known coagulopathy ( p = 0.12), bleeding history ( p = 0.22), or thrombosis history ( p = 0.34). This is the first large multicenter international study comparing POC-INR and P-INR measurements in patients with LVAD and found no statistically significant difference between either methods, particularly when measured within less than 4 hours of each other.